Evolution of Banking System in Albania - Zeneli, Besarta; Bara, Żaneta (Journal of Finance and Financial Law, 2015)
The following article presents banking system in Albania in different aspects. The aim of this paper is to reveal the evolution of the banking system by highlighting the key points of this evolution and showing the major changes Albanian banking system witnessed in different periods. Part of this papers purpose is also the analyses of banking system by using concrete numbers to help the reader understand where does the banking system in Albania stand nowadays. The first part includes basic elements of Albanian banking system, its structure, functions, supervision and legal aspects. The second chapter is based on the evolution of the banking system by revealing chronologically the phases that this system went through before being able to operate in a freeway. To illustrate the situation where the Albanian banking system actually is and how this system operates there are placed graphics and tables prepared based on data from Bank of Albania, The Institute of Statistics and Ministry of Finance. The analysis is made referring a time period of five years, from 2010 to 2014. The results show that from year to year the economic situation is improved, but it still operates under the possible capacity. From the post-communist period to the actual year (2015) the number of banks has increased from three to sixteen banks indicating progress in banking system development. An obvious fact that shows the continual progress is the improvement of the central bank in every upcoming year from 2010 to 2014. Assets and liabilities increase each year of the given period reflecting an expansion of banks activity and its development.